“Waitlist mortality” is high for myeloma patients with limited access to BCMA therapy - Nausheen Ahmed; William Wesson; Muhammad Umair Mushtaq; Rajat Bansal; Haitham AbdelHakim; Sarah Bromert; Allison Appenfeller; Batool Abu Ghazal; Anurag Singh; Sunil Abhyankar; Siddhartha Ganguly; Siddhartha Ganguly; et al. (Frontiers in Oncology, 2023)
BackgroundThe first-in-class approved BCMA CAR-T therapy was idecabtagene vicleucel (ide-cel), approved in March 2021, for RRMM patients who progressed after 4 or more lines of therapy. Despite the promising outcomes, there were limited apheresis/production slots for ide-cel. We report outcomes of patients at our institution who were on the “waitlist” to receive ide-cel in 2021 and who could not secure a slot.MethodsWe conducted a retrospective review of RRMM patients evaluated at the University of Kansas Cancer Center for ide-cel from 3/2021-7/2021. A retrospective chart review was performed to determine patient and disease characteristics. Descriptive statistics were reported using medians for continuous variables. Survival analysis from initial consult was performed using Kaplan-Meier Survival estimator.ResultsForty patients were eligible and were on the “waitlist” for CAR-T. The median follow-up was 14 months (2-25mo). Twenty-four patients (60%) secured a production slot and 16 (40%) did not. The median time from consult to collection was 38 days (8-703). The median time from collection to infusion was 42 days (34-132 days). The median overall survival was higher in the CAR-T group (NR vs 9 mo, p<0.001).Conclusion(s)Many patients who were eligible for ide-cel were not able to secure a timely slot in 2021. Mortality was higher in this group, due to a lack of comparable alternatives. Increasing alternate options as well as improvement in manufacturing and access is an area of high importance to improve RRMM outcomes.